Association between the ratio of placental weight to birthweight and the risk of neurodevelopmental delay in 3-year-Olds: The Japan environment and Children's study. (October 2022) - Mitsuda, Naomi; Eitoku, Masamitsu; Yamasaki, Keiko; J-P, Naw Awn; Fujieda, Mikiya; Suganuma, Narufumi; ,; Kamijima, Michihiro; Yamazaki, Shin; Ohya, Yukihiro; Kishi, Reiko; Yaegashi, Nobuo; et al.
Abstract: Introduction: The ratio of placental weight to birthweight (PW/BW ratio) is well known as a simple indicator of the prenatal intrauterine environment and placental functioning. We assessed the impact of PW/BW ratio on the risk of neurodevelopmental delay in 3-year-olds. Methods: We used data of 71 205 mother–child pairs enrolled in the Japan Environment and Children's Study. Low PW/BW ratio was defined as a PW/BW ratio below the 10th percentile of the study population, high PW/BW ratio was defined as above the 90th percentile, and normal PW/BW ratio was defined as between the low and high PW/BW ratio. Neurodevelopment was assessed using the Japanese translation of the Ages and Stages Questionnaires, third edition. Associations between PW/BW ratio and risk of developmental delay were examined using multivariable models. Results: Compared with boys in the normal PW/BW group, boys in the high PW/BW group had higher risk for developmental delays in all domains except fine motor skills (communication: adjusted risk ratio [aRR], 1.17; 95% confidence interval [CI], 1.04–1.33; gross motor skills: aRR, 1.28; 95% CI, 1.13–1.46; problem solving: aRR, 1.20; 95% CI, 1.09–1.31; personal–social: aRR, 1.26; 95% CI, 1.10–1.43), and boys in the low PW/BW group also had higher risk for developmental delays in some domains. For girls, there was almost no association between PW/BW ratio and developmental delay. Discussion: An unbalanced PW/BW ratio, especially high PW/BW ratio, might indicate intrauterine suboptimality, which affects child neurodevelopment in a sex-specific manner. Highlights: Placental weight/birthweight (PW/BW) ratio is known to reflect placental function. Association between PW/BW ratio and risk of neurodevelopmental delay was examined. High PW/BW ratio was associated with increased risk of developmental delay in boys. Unbalanced PW/BW ratio may indicate intrauterine suboptimality.